Modernization and the Fireplace in Eressos, A Greek Rural Town - Eleftherios Pavlides (Oz, 1983)
In function and in symbol, common houses have traditionally provided a satisfying abode. However, with changing cultural values, owners become dissatisfied with the image of their homes and can go to extraordinary efforts to modernize them...